2022
DOI: 10.3389/fimmu.2022.1058272
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome in multiple myeloma: Mechanisms of progression and clinical applications

Abstract: The gut commensal microbes modulate human immunity and metabolism through the production of a large number of metabolites, which act as signaling molecules and substrates of metabolic reactions in a diverse range of biological processes. There is a growing appreciation for the importance of immunometabolic mechanisms of the host-gut microbiota interactions in various malignant tumors. Emerging studies have suggested intestinal microbiota contributes to the progression of multiple myeloma. In this review, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…Treated with concurrent therapies that significantly alter the composition of the gut microbiota, including immunosuppressants, broad-spectrum antibiotics, etc, these patients commonly had intestinal dysbiosis [ 68 , 69 ]. Indeed, analyses of longitudinal fecal samples demonstrated a loss of bacterial diversity after HSCT [ 70 , 71 , 72 , 73 , 74 ], demonstrating that the diversity of the gut microbiota of MM patients with auto-HSCT lowered before transplantation, and then lowered further during transplantation [ 71 ]. Moreover, MM patients with a low diversity of gut microbiota during transplantation had an impaired transplantation response [ 72 ], while those with a high diversity of gut microbiota had better transplantation results and lower transplant-related mortality [ 71 ].…”
Section: Gut Microbiota and Multiple Myelomamentioning
confidence: 99%
See 2 more Smart Citations
“…Treated with concurrent therapies that significantly alter the composition of the gut microbiota, including immunosuppressants, broad-spectrum antibiotics, etc, these patients commonly had intestinal dysbiosis [ 68 , 69 ]. Indeed, analyses of longitudinal fecal samples demonstrated a loss of bacterial diversity after HSCT [ 70 , 71 , 72 , 73 , 74 ], demonstrating that the diversity of the gut microbiota of MM patients with auto-HSCT lowered before transplantation, and then lowered further during transplantation [ 71 ]. Moreover, MM patients with a low diversity of gut microbiota during transplantation had an impaired transplantation response [ 72 ], while those with a high diversity of gut microbiota had better transplantation results and lower transplant-related mortality [ 71 ].…”
Section: Gut Microbiota and Multiple Myelomamentioning
confidence: 99%
“…During the pretreatment stage of melphalan, a higher abundance of Bacteroides was discovered to be associated with the reduced incidence of severe diarrhea, while a higher abundance of Blautia and Ruminococcus was closely related to severe diarrhea and post-transplant nausea and vomiting [ 73 ]. Meanwhile, the significant susceptibility to bloodstream infections (BSI) remained another toxicity of HSCT with lowered diversity and intestinal dysbiosis [ 74 ]. Studies have reported that with low diversity of gut microbiota and dominance of specific bacteria (mainly enterococcus , streptococcus , and various proteobacteria ), bacteremia remarkedly increased during HSCT [ 75 ].…”
Section: Gut Microbiota and Multiple Myelomamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the challenges of obtaining real-time microbiome data in clinical practice, retrospective studies have started illuminating the relationship between changes in particular microbial characteristic and MM ( Zhang et al, 2022 ). Due to confounding factors such as lifestyle, environment, host gene mutations, and potential reverse causality, the precise association between genes in MM patients and gut microbiota remains underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…The dysbiosis of GM has the potential to induce alterations in GM-derived metabolites, which act as signaling molecules and substrates for immune and metabolic responses. This, in turn, may play a role in the advancement of hematologic malignancies [12]. Recent studies have revealed a considerable reduction in GM diversity in all types of leukemia investigated, that persists even after ve years of survival [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%